STIMULATING THE CREATION OF NEW PRODUCTION TECHNOLOGIES AS A FACTOR OF TECHNOLOGICAL MODERNIZATION - Mingaleva, Zhanna (PEOPLE: International Journal of Social Sciences, 2018)
The task of intensifying efforts to stimulate the process of creating advanced production technologies today is facing the modern economy. To this end, it is necessary to identify those factors that directly influence the creation of new national high technologies for production, regardless of regional specifics and regional policy and irrespective of technology imports. This was set as the research goal in this article.The method of least squares was used to construct an econometric model. A semi-logarithmic model was obtained after all recalculations that best corresponded to the stated research task and the selected criteria for selecting variables.As a result of the research, two factors were identified that are not related to each other, but have a direct impact on the creation of new national high production technologies - a patent issued for inventions and internal R&D expenditures. A purposeful impact on these factors will allow ensuring the technological modernization of the country’s production base, the development of the scientific and technical potential of key sectors and sectors of the economy, and the growth of the country’s intellectual resources.In the future, it is necessary to continue the factor analysis of the process of creating new technologies with the aim of activating and strengthening it. It is necessary to focus on stimulating the process of creating technologies that meet world standards and outrun them.